Optimization of parameters for hardness of brass – AlN composite. (2023) - Jasper, S.; Vijayakumar, D.; Sankarlal, R.L.; Stalin, B.; Rajesh, S.
Abstract: To create a homogeneous material, powder particles were repeatedly cold-welded and fractured in a high energy ball mill to acquire the microstructural study of the brass-AlN composite. In this work, through Mechanical Alloying with varying aluminium nitride weight percentages (AlN) with Brass matrix composites were synthesized. To investigate about their characterization of the brass – AlN composite the milled composite powders underwent the SEM examinations. The SEM analysis proved that AlN was distributed uniformly throughout the Brass matrix. Additionally, it made sure that AlN was distributed evenly throughout the matrix, excluding the pores. While increasing the Sintering temperature to 800 °C and also maintaining the sintering time for 3hrs, the hardness and the density of the brass matrix composites is increased and porosity decreases when AlN is included in the Brass matrix.